Butterflies - Marsh, Laura F.; National Geographic Society (U.S.); National Geographic Channel (Television station : Washington, D.C.) (Washington, D.C. : National Geographic, 2010)
Introduces the migration patterns of monarch butterfies, describing the vast distances they cover, why they migrate, and the dangers they face along the way.
On the move -- Amazing monarchs -- Mighty big trip -- Need to lead -- It takes the whole family -- Danger! -- Tiring travel -- From egg to butterfly -- Munching monarchs -- 10 cool things about monarchs -- At risk -- What you can do.
OSLIS\Gale Nat Geo eBooks(2/2/23).
"National Geographic Channel."
"As seen on the National Geographic Channel"--Cover.
Includes index.
Description based on print version record.
Keywords: Monarch butterfly -- Migration -- Juvenile literature; Monarch butterfly -- Juvenile literature; Monarch butterfly -- Migration; Monarch butterfly; Electronic books- OSLIS; Electronic books